2008
DOI: 10.1021/ci700351y
|View full text |Cite
|
Sign up to set email alerts
|

Gradual in Silico Filtering for Druglike Substances

Abstract: The suitability of decision trees in comparison to support vector machines for the classification of chemical compounds into drugs and nondrugs was investigated. To account for the requirements upon screening virtual compound libraries, schemes for successive filtering steps with gradual increasing computational cost are outlined. The obtained prediction accuracy was similar between decision trees and support vector machine approaches for the applied compound data sets. By using rapidly computable variables su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 63 publications
0
54
0
Order By: Relevance
“…A comprehensive list of these descriptors can be found elsewhere. [20] Additional likeliness scores for each of the three CYP isoforms were generated from the respective substrates and nonsubstrates. The underlying approach is identical to the drug-likeliness index as described earlier in full detail.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive list of these descriptors can be found elsewhere. [20] Additional likeliness scores for each of the three CYP isoforms were generated from the respective substrates and nonsubstrates. The underlying approach is identical to the drug-likeliness index as described earlier in full detail.…”
Section: Methodsmentioning
confidence: 99%
“…For a detailed explanation of the descriptors see the literature. [20] Property CYP3A4 CYP2D6 CYP2C9 [a] Likeliness scores for the respective CYP isoform were computed from the respective substrates and nonsubstrates (see Section 2) [a] Likeliness scores for the respective CYP isoform were computed from the respective substrates and nonsubstrates (see Section 2) It is well known that particularly large molecules are preferentially metabolized by CYP3A4 due to its larger binding pocket compared to the other CYPs. The molecular volume is likewise the primary criterion in Lewis' manually derived classification scheme.…”
Section: Chemical Interpretation Of Selected Descriptorsmentioning
confidence: 99%
“…In order to develop more reliable prediction models of drug-likeness, a large number of molecular descriptors and numerous machine learning approaches have been employed, such as support vector machine (SVM) [40][41][42][43]67], neural networks (NN) [37,38,40,41,67,68], genetic algorithm (GA) [69][70][71], recursive partitioning (RP) [45,72], etc. Encouragingly, most prediction models for drug-likeness predictions established by machine learning approaches show satisfactory abilities to discriminate between drug-like and non-drug-like molecules.…”
Section: Prediction Models Based On Machine Learning Approachesmentioning
confidence: 99%
“…Once identified, each of these discriminating substructures are tested statistically for enriched activity and compared to the privileged substructures reported in the literature. DTs are also used for the classification of chemical compounds into drug and nondrugs [111,324]. In Schneider et al, DT interpretation suggested the main criteria for separating drugs from nondrugs.…”
Section: Decision Treesmentioning
confidence: 99%